Defense Burden and the Effect of Others: From Neighbors to Allies. Issue 8 (17th November 2021) - Xiaoxin, Yang; Bo, Chen
ABSTRACT: This paper presents new evidence on the effects of neighbors and allies on defense burdens using a spatial econometrics model with panel data on 36 countries in Europe collected over 19 years. Apart from the conventional spatial matrices of geographical neighbors, we develop special political vicinity matrices based on arms transfers, which reveal political closeness among countries, and solve the problems associated with endogenous weight matrices by using a QMLE approach. The regression results demonstrate that the defense burden is positively and spatially correlated among geographical neighbors. The use of political vicinity matrices reveals a negative eﬀect of allied relations on defense burdens, which supports the free-riding theory in alliances for setting a defense budget. With composite matrices, the intimidation effect induced by geographical approaches is dominated by the free-riding actions of allies, and the effect becomes more pronounced over time.